ProTide generated long-acting abacavir nanoformulations. Issue 60 (11th July 2018) - Lin, Zhiyi; Gautam, Nagsen; Alnouti, Yazen; McMillan, JoEllyn; Bade, Aditya N.; Gendelman, Howard E.; Edagwa, Benson
Abstract : Single NM3ABC treatment of macrophages produced sustained intracellular carbovir-triphosphate and antiretroviral activities for up to 30 days. Abstract : Abacavir pronucleotide nanoformulations (NM3ABC ) were prepared as a novel long acting slow effective release antiretroviral therapy. Single NM3ABC treatment of human monocyte-derived macrophages produced sustained intracellular carbovir-triphosphate and antiretroviral activities for up to 30 days.